PENGARUH SOSIALISASI PERPAJAKAN TERHADAP KESADARAN PESERTA DIDIK DENGAN PROGRAM TAX GOES TO SCHOOL SEBAGAI VARIABEL MODERATING - Afiah Nuraida (JURNAL EKOBIS DEWANTARA, 2018)
This study aimed to examine to the influence of socialization of taxation to the awareness learners early age in understanding the knowledge of taxation. The Tax Goes To School Programe as a variable that can strengthen or weaken the influence of socialization on taxation against the awareness of learners to understand the knowledge of taxation. The nature of this research is descriptive research with quantitative approach and the use of primary data types. This research was done in the scope of the 1 Banguntapan Bantul Senior High School. The questionnaire was distributed to 100 respondents and data that can be processed are 93 questionnaires. The method of data analysis in this study using simple regression and test the difference in the absolute. The results of the study that the socialization of taxation have a positive effect on the awareness of learness early age indicated by the value of t count of 8,269 with the level of the significance of 0,000. The Tax Goes To School Programe is not able to strengthen the influence of socialization of taxation to the awareness learnes early age indicated by the value of t count of 0,041 with the level of the significance of o,967, so that the Tax Goes To School Programe is homologizer moderating variable.